LEARNING OPEN CV 3 - ADRIAN KAEHLER; GARY BRADSKI (NAVI MUMBAI SHROFF PUBLISHERS & DISTRIBUTORS PVT.LTD, 2017)
OPEN CV IS USED FOR COMMERICAL APPLICATIONS SUCH AS SECURITY,MEDICAL IMAGING, PATTERN AND FACE RECOGNITION,ROBOTICS.
LEARNING OPEN CV 3
COMPUTERS
Keywords: COMPUTERS; COMPUTERS